A Simplified Space-Vector Modulation Algorithm for Four-Leg Npc Converters - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2017)
To interface generation sources and loads to four-wire distribution networks it is important to use power converters and modulation methods, which provide high performance, flexibility, and reliability. To achieve these goals, this paper proposes a simple and efficient space vector modulation (SVM) algorithm in α β γ coordinates for neutral point clamped (NPC) converters. The proposed SVM method reduces a 3-D (α β γ) search amongst modulating vectors into a simple 2-D (α β) problem. Moreover, the algorithm provides full utilization of the dc-link voltage and full utilization of the redundant vectors, and it can be applied to any other four-leg converter topology. The proposed SVM has been successfully validated using a 6-kW three-level four-leg NPC converter, achieving control over the voltages of the dc-link capacitors and a simple definition of the switching patterns for shaping the frequency spectrum. © 1986-2012 IEEE.